ANALYSIS OF DIFFERENTIATED ASSESSMENT BASED ON THE EMANCIPATED CURRICULUM IN JUNIOR HIGH SCHOOL - Paramita, Kadek Candra; Budiarta, Luh Gd Rahayu; Utami, Ida Ayu Made Istri (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2025)
This study aims to analyze differentiated assessment based on the emancipated curriculum in junior high school using descriptive qualitative as the design for this study. The study was conducted in one of the junior high schools in Buleleng Regency in one class with 32 students. The data were collected through teacher interviews and student questionnaires. The teacher interviews consist of twenty-four questions related to emancipated curriculum, assessment, learning methods, diagnostic assessment, formative assessment, summative assessment, and differentiated assessment. The students’ questionnaire consists of eighteen questions (six questions about learning methods and twelve about learning styles). There are four learning styles: visual, auditory, read/write, and kinesthetic. However, the most widely used by students is the auditory learning style